Does Exposure to Animal Cognition Research Influence the Zoo Visitor Experience? - Bonnie M. Perdue (Animal Behavior and Cognition, 2021)
Zoos average about 183 million visitors per year, which makes them a major source for educating the public due to the diverse and wide-ranging demographic that visit. Zoos are increasingly a source of scientific research in a variety of subfields, including animal cognition, although much of this research takes place behind the scenes. Bringing this research to the public perspective has the potential to increase engagement of zoo visitors. However, it is not always possible to show live research, but videos have been found to be an effective educational approach in other domains. Here, we presented a brief video illustrating cognitive research involving sun bears at Zoo Atlanta to determine the potential effect on visitors. We measured several aspects of visitor behavior (stay time and actual behaviors in the exhibit), attitudes (towards both animal research and educational technology), and knowledge gained at the exhibit. We also presented a control video that focused on sun bear enrichment to tease out whether potential effects on visitors were related to the research focus of the video, or merely an effect of a video playing in the exhibit space. Visitor behavior, attitudes, and knowledge were determined by observing a randomly selected visitor’s behavior throughout their time in the exhibit space, and then requesting completion of a survey when they exited the exhibit (N = 148). We compared various aspects of behavior, attitudes, and knowledge across the Scientific Video, Enrichment Video, and No Video conditions. There were no differences between the Scientific Video and the Enrichment Video conditions; however, some differences were found between visitors who experienced a video during their visit (scientific or enrichment video) versus those who did not. Attitudes towards technology in the exhibit space were generally positive. There was also a significant correlation between visitor stay time (overall time spent in the exhibit space) and knowledge gained. Visitors learning about research in zoos remains important, but it is unclear if a video is a sufficient means to share that information.